A tale of two regions: methane emissions from oil and gas production in offshore/onshore Mexico. (26th January 2021) - Zavala-Araiza, Daniel; Omara, Mark; Gautam, Ritesh; Smith, Mackenzie L; Pandey, Sudhanshu; Aben, Ilse; Almanza-Veloz, Victor; Conley, Stephen; Houweling, Sander; Kort, Eric A; Maasakkers, Joannes D; Molina, Luisa T; et al.
Abstract: We use atmospheric observations to quantify methane (CH4 ) emissions from Mexico's most important onshore and offshore oil and gas production regions which account for 95% of oil production and 78% of gas production. We use aircraft-based top-down measurements at the regional and facility-levels to determine emissions. Satellite data (TROPOMI CH4 data and VIIRS night-time flare data) provide independent estimates of emissions over 2 years. Our airborne estimate of the offshore region's emissions is 2800 kg CH4 h −1 (95% confidence interval (CI): 1700–3900 kg CH4 h −1 ), more than an order of magnitude lower than the Mexican national greenhouse gas inventory estimate. In contrast, emissions from the onshore study region are 29 000 kg CH4 h −1 (95% CI: 19 000–39 000 kg CH4 h −1 ), more than an order of magnitude higher than the inventory. One single facility—a gas processing complex that receives offshore associated gas—emits 5700 kg CH4 h −1 (CI: 3500–7900 kg CH4 h −1 ), with the majority of those emissions related to inefficient flaring and representing as much as half of Mexico's residential gas consumption. This facility was responsible for greater emissions than the entirety of the largest offshore production region, suggesting that offshore-produced associated gas is being transported onshore where it is burned and in the process some released to the atmosphere. The satellite-based data suggest even higher emissions for the onshore region than did the temporally constrained aircraft data (>20 times higher than the inventory). If the onshore production region examined is representative of Mexican production generally, then total CH4 emissions from Mexico's oil and gas production would be similar to, or higher than, the official inventory, despite the large overestimate of offshore emissions. The main driver of inaccuracies in the inventory is the use of generic, non-Mexican specific emission factors. Our work highlights the need for local empirical characterization of emissions if effective emissions mitigation is to be undertaken.